2019
DOI: 10.1515/cmb-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Using computational approaches to study dengue virus capsid assembly

Abstract: Dengue viral capsid plays a significant role in viral life cycle of dengue, especially in vial genome protection and virus-cell fusion. Revealing mechanisms of the viral capsid protein assembly may lead to the discovery of anti-viral drugs that inhibit the assembly of the viral capsid. The E and M-proteins are arranged into heterotetramers, which consists of two copies of E and M-protein. The heterotetramers are assembled into a highly ordered capsid. While many investigations of the interactions between E and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Besides the experimental studies, various computational studies have been conducted to investigate the interactions between SARS-CoV-2 S protein and ACE2. Some systematic comparison and analysis were performed on SARS-CoV-2 S protein RBD and ACE2 to identify potential intermediate hosts transmitting SARS-CoV-2 to humans (Salas et al, 2019 ). Some MD simulations revealed that the SARS-CoV-2 S protein-ACE2 binding is more temperature sensitive than SARS-CoV S protein-ACE2 binding (van der Schoot and Bruinsma, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the experimental studies, various computational studies have been conducted to investigate the interactions between SARS-CoV-2 S protein and ACE2. Some systematic comparison and analysis were performed on SARS-CoV-2 S protein RBD and ACE2 to identify potential intermediate hosts transmitting SARS-CoV-2 to humans (Salas et al, 2019 ). Some MD simulations revealed that the SARS-CoV-2 S protein-ACE2 binding is more temperature sensitive than SARS-CoV S protein-ACE2 binding (van der Schoot and Bruinsma, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The charge distribution on capsomers mainly has two functions: First, the electrostatic interactions among capsomers play significant roles in assembling and stabilizing the whole capsid structure (Li et al, 2012a ; Salas et al, 2019 ; Xian et al, 2019 ). Second, electrostatic interactions between capsid and DNA/RNA stabilize the encapsidated genomic materials by neutralizing the repulsive forces between the DNA/RNAs (Bakker et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on viral capsids have demonstrated the interactions between an individual capsomer and its adjacent capsomers are crucial in the capsid assembly process (Salas et al, 2019 ; Xian et al, 2019 ). Here we focused on the interaction between one capsomer and the rest of the capsid.…”
Section: Resultsmentioning
confidence: 99%
“…With the fast developments of computing technology, computational methods have been widely used in drug-related research [12], including protein-protein interactions [13,14], MD simulations [15], coarse-grained models [16], pH dependence of protein-protein interactions [17][18][19][20], etc. Our previous studies have applied multi-scale computational methods to study several pathogens [21][22][23][24][25] including the SARS-CoV-2 viruses [26,27], which revealed some mechanisms of the SARS-CoV-2 S protein. Additionally, many other research groups have made successful progress to understand the SARS-CoV-2 using computational methods [28,29].…”
Section: Introductionmentioning
confidence: 99%